Extrinsic Adenomyosis Is Associated With Postoperative Recurrence of Ovarian Endometrioma - Sun, Man; Xu, Ping; Zou, Gen; Wang, Jianzhang; Zhu, Libo; Zhang, Xinmei (Frontiers in Medicine, 2022)
Objective: To determine whether endometrioma recurrence is closely related to the presence of extrinsic adenomyosis which was demonstrated by magnetic resonance imaging (MRI). Design: Observational cross-sectional study involving patients with recurrence of ovarian endometrioma. Correlations of endometrioma recurrence and adenomyosis subtypes shown by MRI were analyzed. Method: Between January 2018 and December 2020, a total of 233 patients with recurrence of ovarian endometrioma (OMA) after ovarian cystectomy were administered for surgery at our institution. All patients were divided into subtype II (Group A), subtype I+IV (Group B) and non-adenomyosis (Group C) groups at preoperative MRI imaging. The correlations of endometrioma recurrence with clinical features, imaging appearance, and surgical findings were retrospectively analyzed. Results: We found 112 (48.07%) patients of endometrioma recurrence combined with subtype II adenomyosis, 8 (3.43%) subtype I adenomyosis, 47 (20.17%) subtype IV adenomyosis, 66 (28.32%) non-adenomyosis. The mean time of OMA recurrence (44.28 ± 8.37 mon, vs. 63.96 ± 10.28 mon, vs. 69.36 ± 9.34 mon), rate of pain symptoms (85.71%, vs. 69.10%, vs. 18.18%) and primary infertility (31.25%, vs. 14.55%, vs. 10.77%) were higher in Group A. Uterine volume (257.37± 42.61 cm3 vs. 203.14± 33.52 cm3 vs. 100.85± 26.67 cm3) and mean OMA size (4.97 ± 2.25 cm, vs. 4.36±2.38 cm, vs. 4.46±2.70 cm)were significantly larger in Group A. The rate of DIE (83.93% vs. 45.45% vs. 40.91%), the number of DIE (3.6 ± 1.8 vs. 2.3 ± 1.5 vs. 2.2 ± 1.3), the mean total revised American Society for Reproductive Medicine score (rASRM, 103.14±23.89, vs. 74.23±16.72, vs. 36.51±14.23) were significantly higher in Group A. After a multiple logistic regression analysis, extrinsic adenomyosis (OR 2.5,95%CI 1.2-3.4), DIE lesions (OR 2.1, 95%CI 1.4-2.8) and primary infertility (OR 1.8, 95%CI 1.3-4.3) were significantly associated with early recurrence (in 3-year) of OMA. Conclusions: Extrinsic adenomyosis was associated with postoperative recurrence of ovarian endometrioma. In addition, a pathogenic link between extrinsic adenomyosis and pelvic endometriosis needs to be clarified.